Risk factors and associated complications with unplanned intubation in patients with craniotomy for brain tumor. (March 2020) - Li, Yan Icy; Ventura, Nina; Towner, James E.; Li, Kevin; Roberts, Debra E.; Li, Yan Michael
Highlights: Patients undergoing surgical resection of a brain tumor have the potential risk for being intubated post-operatively. Identify risk factors and associated complications for UI in adult patients who underwent a craniotomy for a brain tumor. This risk score could be used to help identify patients at a higher risk and possibly help prevent unplanned intubation. Abstract: Patients undergoing surgical resection of a brain tumor have the potential risk for beingintubated post-operatively, which may be associated with significant morbidity and/or mortality after surgery. This study was analyzed various preoperative patient characteristics, postoperative outcomes, and complications to identify risk factors for unplanned intubation (UI) in adult patients undergoing craniotomy for a brain tumor and created a risk score framework for that cohort. Patients undergoing surgery for a brain tumor were identified according to primary Current Procedural Terminology codes, and information found in The American College of Surgeons (ACS) National Surgical Quality Improvement Project (NSQIP) database from 2012 to 2015 was reviewed. A total of 18, 642 adult brain tumor patients were included in the ACS-NSQIP. The rate of unplanned intubation in this cohort was 2.30% (4 2 8). The mortality rate of patients who underwent UI after surgical resection of brain tumor was 24.78% compared to an overall mortality of 2.46%. During the first 30 days after surgery, 33% of patients who underwent UI had an unplanned reoperation, compared to 4.76% of patients who did not undergo unplanned intubation. Bivariate and multivariate analyses identified several predictors and computed a risk score for UI. A risk score based on patient factors for those undergoing a craniotomy for a brain tumor predicts the postoperative UI rate. This could aid in surgical decision-making by identify patients at a higher risk of UI, while modifying perioperative management may help prevent UI.